Post-traumatic stress disorder : diagnosis, management and treatment - Nutt, David J; Zohar, Joseph; Davidson, Jonathan R. T (Martin Dunitz, 2000)
(Martin Dunitz) Univ. of Bristol, UK. Contents include post-traumatic stress disorder, epidemiology, diagnostic dilemmas, human brain imaging, neuroendocrinology, psychological debriefing, pharmacotherapy, traumatic stress disorders in children, and more. For psychiatrists.
Keywords: traumatologie; psychiatrie